Permanents of 2 x 2 Matrices Modulo n - Bohra, Ayush; Arikatla Satyanarayana Reddy (The PUMP Journal of Undergraduate Research, 2021)
In this article we compute the number of invertible two by two matrices with integer entries modulo n whose permanents are congruent modulo n to a given integer x.